Praecitrullus fistulosus Fruit Extract Ameliorates Type II Diabetic Complications in Rats: In Silico, In Vitro, and In Vivo Investigation - Mishra, Shanti Bhushan; Verma, Juhi; Sahu, Garima; Gupta, Nishi (Sciences of Pharmacy, 2025)
This study explored the safety and antidiabetic potential of a hydroalcoholic extract of Praecitrullus fistulosus fruits, along with qualitative and quantitative phytochemical analyses. The antidiabetic effect was evaluated using in vitro methods, including α-amylase and α-glucosidase inhibition assays, as well as an in vivo high-fat diet and low-dose streptozotocin-induced diabetic model. Molecular docking studies were conducted to identify phytochemicals responsible for the antidiabetic effects. The fruit extract exhibited maximum inhibition of 52.06% and 58.10% for α-amylase and α-glucosidase enzymes, respectively, at a concentration of 100 µg/mL. The extract also demonstrated a significant (p < 0.001) and dose-dependent antidiabetic effect at oral doses of 200 mg/kg and 400 mg/kg in the tested animals. In silico analysis revealed that α-tocopherol exhibited the best docking pose, with a docking energy of -8.2 kcal/mol. Based on the results, it can be concluded that the hydroalcoholic extract of Praecitrullus fistulosus contains phytochemicals effective in controlling glucose levels. This study also validates the traditional use of Praecitrullus fistulosus fruits in managing diabetes.